Image Processing Technology in Book Metadata Extraction System Using Optical Character Recognition (OCR) - Andi Emil Multazam; Akhmad Qashlim; Muhammad Sarjan (Institut Teknologi dan Bisnis Bina Sarana Global, 2023)
Extracting book metadata by retyping the identity of the book, such as the author's name, book title, publisher, and several other identities, is a routine that is carried out repeatedly at the Polewali Mandar district library, this activity takes much of time, using several staff and it turns out that this activity has much potential for input errors. Errors in extracting book metadata will result in errors in the book repository system database, resulting in difficulty finding and using books or book data information. This problem can be solved by creating a book metadata extraction system using image processing technology and OCR. This study aims to design a scanner technology to extract book metadata. Accuracy is carried out in 2 stages, the first validation of image extraction results using the ROC method and the second validation by directly matching the result of extracting the book's metadata with the actual book. The results of this study indicate that the system has worked with an accuracy of 98.78% with an average detection time of 1.49 seconds and has succeeded in presenting the extraction results on the website page. Thus the metadata extraction system with the OCR method can be applied to libraries to input book data.